Evaluation of myocardial involvement in patients with connective tissue disorders: a multi-parametric cardiovascular magnetic resonance study. Issue 1 (January 2017) - Mayr, Agnes; Kitterer, Daniel; Latus, Joerg; Steubing, Hannah; Henes, Joerg; Vecchio, Francesco; Kaesemann, Philipp; Patrascu, Alexandru; Greiser, Andreas; Groeninger, Stefan; Braun, Niko; Alscher, M.; et al.
Abstract Background Severe arrhythmias or heart failure may be surrogates of myocardial involvement in patients with connective tissue disorders (CTD). However, most patients present with unspecific symptoms, normal ECG, and preserved left ventricular ejection fraction (LV-EF). Therefore, timely diagnosis by an accurate technique is crucial. Late gadolinium enhancement (LGE) cardiovascular magnetic resonance (CMR) has proven value for the detection of focal processes, but due to the often diffuse character of fibrosis/inflammation in CTD patients, CMR mapping techniques might be of incremental value for the assessment of myocardial involvement. Purpose of this study was to evaluate a multi-parametric CMR protocol as a screening tool for myocardial involvement in CTD patients. Methods Forty CTD patients were prospectively enrolled and underwent CMR, twenty healthy volunteers served as control group. Results Mean LV-EF was 62 %; LGE prevalence was low (18 %). CTD patients had higher native T1 (1008 vs. 962 ms, p = 0.001), lower post contrast T1 (494 vs. 526 ms, p = 0.008), expanded extracellular volume (ECV) (28 vs. 25 %, p = 0.001), and higher T2 values (53 vs. 49 ms, p < 0.001) compared to controls. Among patients with values higher than the 95 % percentile of healthy controls, native T1 and T2 values seem to be the most promising discriminators. Conclusion CTD patients showed higher T1, ECV, and T2 values compared to controls, with most significant differences for native T1 and T2, which seem to be independent of the presence of LGE. Our data suggest that CMR mapping techniques are of incremental value in the detection of myocardial involvement in CTD patients.